Evaluation of the antioxidant activity by the DPPH radical scavenging method of free and liposome-associated cocoa extracts - Nascimento, Daniela Alves de Oliveira; Raffin, Renata Platcheck; Fogaça, Aline de Oliveira; Moraes, Cristina Machado Bragança de; Boligon, Aline; Ourique, Aline Ferreira (Disciplinarum Scientia | Naturais e Tecnológicas, 2017)
Polyphenols have benefits to health, as a potent antioxidant action, however, such benefits can be committed due to the instability facing the different conditions. In this sense, the nanoencapsulation is a tool that allows imprisoning compounds with activity, protecting them against degradation and improving stability. This way, the aim of this work was to identify and to quantify the cocoa compounds, to nanoencapsulate them and to evaluate the antioxidant activity in comparison to the raw extract. The chromatographic analysis showed that the predominant flavonoids in the cocoa extract were the epicatechin, epigallocatechin, isochercetin and the kaempferol. Liposomes were produced by the reverse phase evaporation method and present adequate nanometric characteristics. The antioxidant activity, EC50, from liposomes containing cocoa extract was superior to the one from the free extract, demonstrating the liposome efficiency in protecting the active and improve its activity.